Analisis Tingkat Kesehatan Bank Menggunakan Metode Rgec (Risk Profile, Good Corporate Governance, Earnings, dan Capital) pada Bank Umum BUMN Periode 2018-2020 - Muhamad Bayu Nur Rohman (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. This study aims to determine the health level of BUMN Commercial Banks from the aspects of Risk Profile, Good Corporate Governance, Earnings, Capital and RGEC as a whole. The author uses 4 sample companies with a time period of 2018-2020. This research uses descriptive quantitative research methods. The data analysis technique used is descriptive analysis with reference to POJK No. 4/POJK.03/2016. The results showed that in terms of the Risk Profile, the NPL ratio of BUMN Commercial Banks for the 2018-2020 period was categorized as